Expression of the polycomb-group gene BMI1 is related to an unfavourable prognosis in primary nodal DLBCL. Issue 2 (12th July 2006) - van Galen, Joost C; Muris, Jettie J F; Oudejans, Joost J; Vos, Wim; Giroth, Cindy P E; Ossenkoppele, Gert J; Otte, Arie P; Raaphorst, Frank M; Meijer, Chris J L M
Abstract : Background: : Clinical outcome in patients with diffuse large B cell lymphomas (DLBCL) is highly variable and poorly predictable. Microarray studies showed that patients with DLBCL with a germinal centre B cell-like (GCB) phenotype have a better prognosis than those with an activated B cell-like (ABC) phenotype. The BMI1 proto-oncogene was identified as one of the genes present in the signature of the ABC type of DLBCL, associated with a poor prognosis. Objectives: : (1) To investigate, in primary nodal DLBCL, the expression of BMI1 and its association with clinical outcome and DLBCL signature; (2) to look for an association between BMI1 expression and the expression of its putative downstream targets p14ARF and p16INK4a . Results: : BMI1 expression was found to be associated with poor clinical outcome, but not clearly with an ABC-like phenotype of DLBCL. Expression of BMI1 was frequently, but not always, related to low levels of expression of p14ARF and p16INK4a . Conclusion: : Expression of BMI1 is associated with an unfavourable clinical outcome of primary nodal DLBCL.